Relações entre grau de perda auditiva e as habilidades de linguagem em crianças usuárias de AASI - Pereira, Regiane da Silva (2023)
Introduction: The literature points out that vocabulary is linked to speech perception, considering that the individual is dependent on good discrimination to have access to information. In children with hearing loss, obstacles distance them from typical development, reflecting on the gap in auditory skills generated by stimulus deprivation, leaving them below expectations, making it difficult to equate their results to a child with normal hearing. The auditory perception and the development of the repertoire in these cases are directly influenced by the consistent use of the devices, with significant repercussions on the development in early childhood. Objective: To analyze the role of audibility for speech sounds in auditory perception and language development and to identify how consistency in device use can interfere in this process. Method: The procedures were performed at CeAC/Derdic/PUCSP. Speech Intelligibility Indexes (SII) were established for input sounds of 55 and 65 dB SPL of 29 children with sensorineural hearing loss who use hearing aids bilaterally and have oral language. They were submitted to the task of repetition of words with and without meaning in two different intensities (55 and 65 dBSPL) and to the Peabody Picture Vocabulary Test – PPVT for the study of one of the vocabulary aspects. In data analysis, the SII was related to the results obtained in each analysis criterion. Results: The percentage of correct answers in all lists was not related to SII 65dB, probably because almost all children had SII65dB>= 64%. In the SII55dB, the group of children with SII 55 dB ≥ 64% had a higher percentage of correct answers, when compared to children in the SII 55 dB < 64% group, in all considered lists. The group with Peabody ≥ 85 has more hits in the lists and tend to have more correct word hits in the lists. The group of children with SII 55dB ≥ 64% are more frequent among those with worse hearing aid use consistency (less than 8 hours/day). Conclusion: For children with moderate hearing loss, the SII at 55dB is more sensitive to assess auditory perception for speech in hearing aid users. Children with SII 55dB lower than 64% make more consistent use of hearing aids. Although there was no significant relationship between SII 65dB and 55 dB with vocabulary skills, the group with a standard score on the PPVT >= 85 had a higher accuracy of words in the lists presented in 65dBNPs, highlighting that the type of loss and the configuration influence in the performance of these children. Further research is needed to determine the audibility limits for speech sounds with a view to improving family orientation processes with the aim of greater consistency in the use of the device